1999
DOI: 10.1002/(sici)1522-726x(199903)46:3<282::aid-ccd5>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous intracoronary ultrasound and Doppler flow studies distinguish flow-mediated from receptor-mediated endothelial responses

Abstract: Abnormalities in vascular endothelial function, which occur early in atherosclerosis, may play an etiologic role in the development of the disease or represent a marker for the extent of atherosclerosis. Endothelial dysfunction, usually characterized by demonstration of decreased endothelium‐dependent vasorelaxation, may be a sensitive and specific method to detect vascular disease in its earliest stages. In this context, separation of abnormalities in receptor‐mediated and flow‐mediated endothelium‐dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…With this methodology, this technique has been shown to distinguish between epicardial and microvascular responses 7 and between agonist-mediated and flowmediated endothelium-dependent responses. 8 In longitudinal studies, we have shown that endothelial dysfunction predicts future progression of coronary intimal thickening in heart transplant patients, with microvascular responses to acetylcholine being stronger predictors than large-vessel responses. The present study reports the relationship between coronary endothelial dysfunction and the clinical end points of angiographically significant coronary allograft vasculopathy, ischemic events, and death in heart transplant recipients.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…With this methodology, this technique has been shown to distinguish between epicardial and microvascular responses 7 and between agonist-mediated and flowmediated endothelium-dependent responses. 8 In longitudinal studies, we have shown that endothelial dysfunction predicts future progression of coronary intimal thickening in heart transplant patients, with microvascular responses to acetylcholine being stronger predictors than large-vessel responses. The present study reports the relationship between coronary endothelial dysfunction and the clinical end points of angiographically significant coronary allograft vasculopathy, ischemic events, and death in heart transplant recipients.…”
supporting
confidence: 91%
“…Continuous measurement of both parameters allowed for calculation of the maximal response, and we have shown that maximal area and flow responses do not occur at the same time. 8 In addition, epicardial responses were measured at only one point in the proximal portion of the coronary tree. Although CAV is a diffuse process, there is good evidence for segmental heterogeneity in endotheliumdependent responses in different coronary arteries and at different sites in the same coronary artery.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Correlations between the degree of vasodilator responses to NTG and the baseline cross-sectional area and age were also seen in our study (Fig. 6), which has been noted in previous studies (10,32,33). Interestingly, even in the healthy subjects, those with lower vasodilation (Ͻ20% area change, n ϭ 7) had a higher mean age (38 Ϯ 2 years) compared to those with Ͼ20% area vasodilation (mean age 30 Ϯ 3 years, n ϭ 12).…”
Section: Discussionmentioning
confidence: 99%
“…Impaired coronary vasodilation to nitroglycerin (NTG), an endotheliumindependent vasodilator, has also been found in patients who have coronary risk factors (9) and has also been associated with an increased risk of future cardiac events (7). However, previous studies have required either invasive X-ray coronary angiography (XRA) (1,4 -8) or intravascular ultrasound (10) to measure epicardial coronary vasodilator responses. A noninvasive technique for measuring human epicardial coronary vasodilation directly would allow more widespread study of coronary vasoreactivity in patients with, or at risk for, coronary artery disease (CAD).…”
mentioning
confidence: 99%
“…Intravascular ultrasound analysis has been used successfully in combination with intracoronary Doppler to differentiate between flow-mediated and receptor-mediated endothelial function [38]. Still, these analyses can only evaluate the response of a small area of the epicardial artery.…”
Section: Coronary Vasoreactivity Studiesmentioning
confidence: 99%